15.3% Efficiency All‐Small‐Molecule Organic Solar Cells Achieved by a Locally Asymmetric F, Cl Disubstitution Strategy. Issue 8 (22nd February 2021) - Hu, Dingqin; Yang, Qianguang; Zheng, Yujie; Tang, Hua; Chung, Sein; Singh, Ranbir; Lv, Jie; Fu, Jiehao; Kan, Zhipeng; Qin, Bo; Chen, Qianqian; Liao, Zhihui; et al.
Abstract: Single junction binary all‐small‐molecule (ASM) organic solar cells (OSCs) with power conversion efficiency (PCE) beyond 14% are achieved by using non‐fullerene acceptor Y6 as the electron acceptor, but still lag behind that of polymer OSCs. Herein, an asymmetric Y6‐like acceptor, BTP‐FCl‐FCl, is designed and synthesized to match the recently reported high performance small molecule donor BTR‐Cl, and a record efficiency of 15.3% for single‐junction binary ASM OSCs is achieved. BTP‐FCl‐FCl features a F, Cl disubstitution on the same end group affording locally asymmetric structures, and so has a lower total dipole moment, larger average electronic static potential, and lower distribution disorder than those of the globally asymmetric isomer BTP‐2F‐2Cl, resulting in improved charge generation and extraction. In addition, BTP‐FCl‐FCl based active layer presents more favorable domain size and finer phase separation contributing to the faster charge extraction, longer charge carrier lifetime, and much lower recombination rate. Therefore, compared with BTP‐2F‐2Cl, BTP‐FCl‐FCl based devices provide better performance with FF enhanced from 71.41% to 75.36% and J sc increased from 22.35 to 24.58 mA cm −2, leading to a higher PCE of 15.3%. The locally asymmetric F, Cl disubstitution on the same end group is a new strategy to achieve high performance ASM OSCs. Abstract : Single‐junction all‐small‐molecule organic solar cells with record high PCEs of 15.3% have been demonstrated by a locally asymmetric electron acceptor BTP‐FCl‐FCl and BTR‐Cl donor.